“Uma Copacabana Perdida nos Confins suburbanos”: a ideia de balnearização do bairro de Ramos/RJ (anos 1920-1940) - Maria Isabel de Jesus Chrysostomo (Confins)
In this article we discuss the internalization in the metropolis of Rio de Janeiro, a habit that has become a carioca brand: to bathe, to expose one's body on the beach and to practice marine sports. We will show how the suburban neighborhoods of Rio absorbed and adapted this model, starting from the analysis of the Ramos district which, between the 1920s and the 1940s, has established a housing estate with a kind of Avenida Beira-Mar. “Lost in the suburban borders”, the picturesque beach of Ramos, sold as the main attribute of this subdivision, becomes both a place of leisure and residence.